Universal Design for Learning in Tertiary Education: Australian Professionals' Perspectives on Using UDL in Practice - Leif, Erin; Gigliotti, Amanda; McClennan, Darlene (Journal of University Teaching and Learning Practice, 2025)
This study explored how tertiary education professionals in Australia understand and apply Universal Design for Learning (UDL) in their practice, the barriers they face, and what more institutions can do to support its implementation. Semi-structured interviews were conducted with 11 professionals across various roles and institutions. Findings revealed that, while educators are using UDL principles to enhance engagement, accessibility, and assessment flexibility, their efforts are often ad hoc and unsupported by formal structures. Key barriers included limited time, confusion about how to apply UDL in specific contexts, and a lack of institutional mandates. Participants strongly advocated for embedding UDL into institutional policies, performance expectations, and strategic plans. Practical, discipline-specific professional learning and access to real-world examples were seen as critical for supporting implementation. The importance of local communities of practice and mindset shifts, positioning UDL as quality teaching for all students, were also discussed. These findings underscore the need for tertiary institutions to adopt a systemic and sustained approach to UDL, moving beyond compliance to embed inclusive design into the fabric of teaching and learning.